The Effect Of Implementation Of Patient Identification Based On The Pall Accreditation Standards On Improving The Patient Safety Program At Royal Prima General Hospital In 2022 - Yosiana Silalahi; Sri Wahyuni Nasution; Chrismis Novalinda Ginting (CV. Inara, 2022)
Patient safety is a variable to measure and evaluate the quality of nursingservices that have an impact on health services. One of the safety services inhospitals starts from the accuracy of patient identification. Patientidentification errors at the beginning of the service will continue to the nextservice error. The purpose of this study was to determine how the effect ofimplementing patient identification based on JCI accreditation standards onimproving the Patient Safety program at Royal Prima Hospital. This type ofresearch is a quantitative study with a cross-sectional design. Samplingtechnique The sampling technique in this study was to use the Slovinformula with a total sample of 124 patients. Data analysis in this study usedunivariate and bivariate analysis. The results of the study explained thatthere was an influence between the implementation of patient identificationbased on the Plenary accreditation standard to the improvement of thePatient Safety program at the Royal Prima Hospital Medan with ap value of<0.007. Through this research, it is hoped that the Royal Prima HospitalMedan can improve the quality of nursing services, especially in theimplementation of identification based on the Plenary AccreditationStandards.